The Complex Relations between Organization and Disorganization and Their Conceptual System. (28th November 2021) - Wu, Kun; Zhang, Shan; Wu, Tianqi
Abstract : For improving and developing self-organization theory in contemporary complex information systems theory, it is necessary to reinterpret related concepts and their relations and construct a conceptual system related to self-organization theory. Based on the latest research results, this article specifically discusses concepts of organization and disorganization, static organization and dynamic organization, static disorganization and dynamic disorganization, organizing and disorganizing, self-organization and other-organization, self-disorganization and other-disorganization, and their relations. Further, it explores the mechanism of organization and disorganization, the compatibility of organization and disorganization, feedback and mutual other-disorganization in interaction, constraint and freedom of organization and disorganization, complexity of restraint and external factors, and relations between "the good" and "the evil" in restraint and freedom. On this basis, a diagram of the conceptual system of organization and disorganization, including four levels and their relations, is presented.